Taxonomic discordance of immersive realities in dentistry: A systematic scoping review - Khaled Q. Al Hamad (21768251) (2024)
Objectives This review aimed to map taxonomy frameworks, descriptions, and applications of immersive technologies in the dental literature. Data The Preferred reporting items for systematic reviews and meta-analyses extension for scoping reviews (PRISMA-ScR) guidelines was followed, and the protocol was registered at open science framework platform (https://doi.org/10.17605/OSF.IO/H6N8M). Sources Systematic search was conducted in MEDLINE (via PubMed), Scopus, and Cochrane Library databases, and complemented by manual search. Study selection A total of 84 articles were included, with 81 % between 2019 and 2023. Most studies were experimental (62 %), including education (25 %), protocol feasibility (20 %), in vitro (11 %), and cadaver (6 %). Other study types included clinical report/technique article (24 %), clinical study (9 %), technical note/tip to reader (4 %), and randomized controlled trial (1 %). Three-quarters of the included studies were published in oral and maxillofacial surgery (38 %), dental education (26 %), and implant (12 %) disciplines. Methods of display included head mounted display device (HMD) (55 %), see through screen (32 %), 2D screen display (11 %), and projector display (2 %). Descriptions of immersive realities were fragmented and inconsistent with lack of clear taxonomy framework for the umbrella and the subset terms including virtual reality (VR), augmented reality (AR), mixed reality (MR), augmented virtuality (AV), extended reality, and X reality. Conclusions Immersive reality applications in dentistry are gaining popularity with a notable surge in the number of publications in the last 5 years. Ambiguities are apparent in the descriptions of immersive realities. A taxonomy framework based on method of display (full or partial) and reality class (VR, AR, or MR) is proposed. Clinical significance Understanding different reality classes can be perplexing due to their blurred boundaries and conceptual overlapping. Immersive technologies offer novel educational and clinical applications. This domain is fast developing. With the current fragmented and inconsistent terminologies, a comprehensive taxonomy framework is necessary. Other Information Published in: Journal of Dentistry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jdent.2024.105058